Pengaruh Media Sosial Terhadap Tingkat Stres Remaja - Najwa, Azzura Aidenia Ardatien; Zidni Fauziyyah Al Ghifari; Naiima Khairiya Ismah; Ati Kusmawati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Social media has become an essential aspect of modern teenagers' lives, offering communication convenience but also introducing new mental health challenges. This study aims to examine the influence of social media on adolescent stress levels using a literature review approach. The findings indicate that excessive social media use can lead to stress due to social pressure, self-comparison, cyberbullying, and the fear of missing out (FOMO). While social media can support self-expression and creativity, its negative effects cannot be overlooked. Therefore, preventive strategies such as limiting screen time, strengthening social support systems, and increasing parental involvement are crucial in guiding teens toward healthier and more balanced digital media use. These efforts are expected to promote better psychological well-being among adolescents in the digital era.